Pyrochlore-Supergroup Minerals Nomenclature: An Update - Atencio, Daniel (Frontiers in Chemistry, 2021)
The general formula of the pyrochlore-supergroup minerals is A2B2X6Y. The mineral names are composed of two prefixes and one root name (identical to the name of the group). The first prefix refers to the dominant anion (or cation or H2O or vacancy) of the dominant valence at the Y-site. The second prefix refers to the dominant cation of the dominant valence [or H2O or vacancy] at the A-site. Thirty-one pyrochlore-supergroup mineral species are currently distributed into four groups [pyrochlore (B = Nb, X = O), microlite (B = Ta, X = O), roméite (B = Sb5+, X = O), and elsmoreite (B = W, X = O)] and two unassigned members [hydrokenoralstonite (B = Al, X = F) and fluornatrocoulsellite (B = Mg, X = F)]. However, when the new nomenclature system of this supergroup was introduced (2010) only seven mineral species, namely, oxycalciopyrochlore, hydropyrochlore, hydroxykenomicrolite, oxystannomicrolite, oxystibiomicrolite, hydroxycalcioroméite, and hydrokenoelsmoreite, were valid. The seven species belong to the cubic crystal system and space group Fd3¯m and O is predominant in the X structural site. The 24 new mineral species described between 2010 and 2021 are cesiokenopyrochlore, fluorcalciopyrochlore, fluornatropyrochlore, hydrokenopyrochlore, hydroxycalciopyrochlore, hydroxynatropyrochlore, hydroxykenopyrochlore, hydroxymanganopyrochlore, hydroxyplumbopyrochlore, fluorcalciomicrolite, fluornatromicrolite, hydrokenomicrolite, hydroxycalciomicrolite, kenoplumbomicrolite, oxynatromicrolite, oxycalciomicrolite, oxybismutomicrolite, fluorcalcioroméite, hydroxyferroroméite, oxycalcioroméite, oxyplumboroméite, fluornatrocoulsellite, hydrokenoralstonite, and hydroxykenoelsmoreite. Among the new species, hydroxycalciomicrolite belongs to a different space group of the cubic system, i.e., P4232. There are also some mineral species that crystallize in the trigonal system. Hydrokenoelsmoreite occurs as 3C (Fd3¯m) and 6R (R3¯) polytypes. Hydrokenomicrolite occurs as 3C (Fd3¯m) and 3R (R3¯m) polytypes, of which the latter corresponds to the discredited “parabariomicrolite.” Fluornatrocoulsellite crystallizes as 3R (R3¯m) polytype. Surely there are several new pyrochlore-supergroup minerals to be described.